The production of electricity from dual-chambered microbial fuel cell fueled by old age leachate. Issue 11 (2nd June 2016) - Cetinkaya, Afsin Y.; Ozkaya, Bestami; Taskan, Ergin; Karadag, Dogan; Cakmakci, Mehmet
ABSTRACT: In this study, electricity production from old age landfill leachate was investigated using dual chambered microbial fuel cell with Ti-TiO2 electrodes. The effect of organic loading rate on microbial fuel cell performance was examined by changing the hydraulic retention time and leachate chemical oxygen demand (COD) concentration. Microbial diversity at different conditions was studied using PCR-DGGE profiling of 16 sRNA fragments of microorganisms in the liquid media of the anode chamber and of the biofilm on the anode electrode. Both COD removal and current density were positively affected with increasing organic loading rate. The highest microbial fuel cell performance was achieved at hydraulic retention time of 0.5 day and organic loading rate of 10 g COD/L.day. The performance of the microbial fuel cell reactor decreased when hydraulic retention time was reduced to 0.25 day. The investigation of the microbial dynamics indicated that abundance of bacterial species was considerably dependent on the operational conditions. The microbial fuel cell reactor was mainly dominated by Geobacter, Shewanella, and Clostridium species, and some bacteria were easily washed out at lower hydraulic retention times.